2016
DOI: 10.1002/chem.201504057
|View full text |Cite
|
Sign up to set email alerts
|

Tilting and Tumbling in Transmembrane Anion Carriers: Activity Tuning through n‐Alkyl Substitution

Abstract: Anion transport by synthetic carriers (anionophores) holds promise for medical applications, especially the treatment of cystic fibrosis. Among the factors which determine carrier activity, the size and disposition of alkyl groups is proving remarkably important. Herein we describe a series of dithioureidodecalin anionophores, in which alkyl substituents on one face are varied from C0 to C10 in two‐carbon steps. Activities increase then decrease as the chain length grows, peaking quite sharply at C6. Molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Calculated values of side-chain rotational correlation times of three aromatic dipeptides demonstrated extremely large slowing with peptide membrane insertion relative to solution (43). It was shown recently that the intrinsic activity of dithioureidodecalin anion carriers is remarkably sensitive to alkyl substitution, passing through a maximum as the chain length increased (44). Molecular dynamics simulations showed that the addition of two hydrocarbon chains tended to turn transporter/ complex, pulling the polar region away from the interface.…”
Section: Discussionmentioning
confidence: 94%
“…Calculated values of side-chain rotational correlation times of three aromatic dipeptides demonstrated extremely large slowing with peptide membrane insertion relative to solution (43). It was shown recently that the intrinsic activity of dithioureidodecalin anion carriers is remarkably sensitive to alkyl substitution, passing through a maximum as the chain length increased (44). Molecular dynamics simulations showed that the addition of two hydrocarbon chains tended to turn transporter/ complex, pulling the polar region away from the interface.…”
Section: Discussionmentioning
confidence: 94%
“…It has been shown recently that the orientation of anion carriers (dithioureido decalins) at the membrane surface contributes significantly to the rate of chloride permeation through the lipid membrane. 42 The bound transporter and chloride complex oriented their polar regions towards the membrane interface and are able to exhibit effective polar interactions with the phospholipid head groups or with bound water molecules. These polar interactions must be broken before the transporter/complex can pass through the membrane, and therefore contribute a substantial potential barrier to the translocation.…”
Section: Discussionmentioning
confidence: 99%
“…An important goal in this area is the development of anion carriers that are (a) highly active, (b) easily synthesized, and (c) readily delivered to bilayer membranes. We have shown that ureas and thioureas in the cholapod ( 1 ) and trans ‐decalin ( 2 ) series (Figure ) can serve as highly effective chloride transporters in large unilamellar vesicles (LUVs). The most powerful, such as bisthioureas 1 b and 2 b (Figure ), can promote significant Cl − /NO 3 − exchange when present as single molecules in LUV membranes .…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Synthetic anion transporters (anionophores) that can mimic the functiono fe ndogenousi on transport proteins could potentially be used to treat these conditions and their development has become an active area of supramolecular chemistry. [4,11,12] An important goal in this area is the development of anion carriers that are (a) highly active, (b) easily synthesized, and (c) readilyd elivered to bilayer membranes.W eh ave shown that ureas and thioureas in the cholapod (1) [13][14][15][16][17][18][19] and trans-decalin (2) [15,17,[20][21][22] series ( Figure 1) can serve as highly effective chloride transporters in large unilamellar vesicles (LUVs). The most powerful, such as bisthioureas 1b and 2b (Figure 2), can promote significant Cl À /NO 3 À exchange whenp resent as single molecules in LUV membranes.…”
Section: Introductionmentioning
confidence: 99%